Beta transformation of the Exponential-Gaussian distribution with its properties and applications - Tesfaw, Kumlachew Wubale; Goshu, Ayele Taye (Frontiers in Applied Mathematics and Statistics, 2024)
This study introduces a five-parameter continuous probability model named the Beta-Exponential-Gaussian distribution by extending the three-parameter Exponential-Gaussian distribution with the beta transformation method. The basic properties of the new distribution, including reliability measure, hazard function, survival function, moment, skewness, kurtosis, order statistics, and asymptotic behavior, are established. Using the acceptance-rejection algorithm, simulation studies are conducted. The new model is fitted to the simulated and real data sets, and its performance is reported. The Beta-Exponential-Gaussian distribution is found to be more flexible and has better performance in many aspects. It is suggested that the new distribution would be used in modelling data having skewness and bimodal distribution.